Antagonistic roles of cGAS/STING signaling in colorectal cancer chemotherapy - Liang, Beiyuan; Xing, Xuanxuan; Storts, Hayden; Ye, Zhen; Claybon, Hazel; Austin, Ryan; Ding, Rachel; Liu, Bei; Wen, Haitao; Miles, Wayne O.; Fishel, Richard; Wang, Jing J. (Frontiers in Oncology, 2024)
FOLFOX, composed of 5-FU, oxaliplatin and leucovorin, is a first line chemotherapy regimen for colorectal cancer (CRC) treatment. In this study, we show that 5-FU and oxaliplatin induce DNA damage and activate cGAS/STING signaling leading to enhanced expression of interferon (IFN) β, IFN-stimulated genes and inflammatory cytokines in mouse and human colon cancer cells as well as increased intratumoral CD8+ T cells in mice. Crucially, 5-FU and oxaliplatin increase PD-L1 expression at the mRNA and protein levels, which has been shown to inhibit CD8+ T cell function. Depletion of cGAS, STING, IRF3, or IFNα/β receptor 1 (IFNAR1) abolishes this increase, indicating that 5-FU/oxaliplatin mediated upregulation of PD-L1 expression is dependent on tumor cell intrinsic cGAS/STING signaling. These results imply opposing roles for FOLFOX during cancer treatment. On one hand, 5-FU and oxaliplatin activate the innate immune response to facilitate anti-tumor immunity, and conversely upregulate PD-L1 expression to evade immune surveillance. Analysis of TCGA colon cancer dataset shows a positive correlation between expression of PD-L1 and components of the cGAS/STING pathway, supporting a role for cGAS/STING signaling in upregulating PD-L1 expression in colon cancer patients. Tumor studies in syngeneic immune competent mice demonstrate that the combination of 5-FU/oxaliplatin and anti-PD-1 significantly reduced tumor growth of colon cancer cells compared to 5-FU/oxaliplatin treatment alone. Taken together, our studies have identified a unique pathway leading to chemoresistance and provide a rationale to combine FOLFOX with anti-PD-1/PD-L1 as an effective CRC treatment.